COVID-19 PANDEMIC AND CREATIVITY: REFLECTIONS AND LESSONS FOR TOURIST CITIES, BY GREG RICHARDS - Mediotte, Elias; Richards, Greg (Brazilian Creative Industries Journal, 2022)
There is a growing debate about the use of creativity for sustainable development, particularly in terms of increasing the creative potential of cities. However, studies based on the experiences and perspectives of leading authors in this area are limited. Greg Richards is a long-standing researcher on the application of creativity in various socio-economic sectors, including creative tourism, creative cities, economy, and creative industries. This study, based on a semi-structured interview conducted with Greg Richards, seeks to present some reflections and ideas for ways forward, considering the scenario before, during, and after the Covid-19 pandemic and its possible effects on the new economy. Particular attention is paid to the emerge of ‘glocal’ creativity, especially related to the UNESCO Creative Cities.